Have a doubt with this?

For all positive integers n n , if the fractional part of 3 2 n 8 \frac{3^{2n}}{8} is of the form p q \frac pq for coprime positive integers p , q p,q , find the value of p + q p+q .


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Akash Gaonkar
May 9, 2015

Let us begin by simplifying the problem. Ignoring our final addition, we seek positive coprime integers p, q such that the fractional remainder of p / q p/q equals 3 2 n / 8 , n Z + 3^{2n}/8, n \; \in \mathbb{Z}^+ .

In other words, we want to find p / q = 3 2 n ( m o d 8 ) 8 p/q = \frac{3^{2n}\ (mod\ 8)}{8} . "mod" stands for modulus, or the remainder when divided by. 5 (mod 2) is 1, 6 (mod 7) is 6, and 9 (mod 8) is 1. In general, a = b ( m o d c ) , a , b , c Z + , b < c a = b\ (mod\ c), a,b,c \in \mathbb{Z}^+, b < c if n Z + : a = c n + b . \exists n\ \in \mathbb{Z}^+: a = cn + b.

Since p p and q q are coprime, we know that p = 3 2 n ( m o d 8 ) p = 3^{2n}\ (mod\ 8) and q = 8 q = 8 .

Simplifying, p = 9 n ( m o d 8 ) p = 9^n\ (mod\ 8) , or the remainder of 9 n 9^n when divided by 8 8 . This suggests that 9 n ( m o d 8 ) 9^n\ (mod\ 8) is some constant; in fact, 9 n ( m o d 8 ) = 1 9^n\ (mod\ 8) = 1 . This is proven below.

p = 1 , q = 8 p + q = 9. p = 1, q = 8 \Rightarrow p + q = 9. QED.

\\ \\

Proof that 9 n ( m o d 8 ) = 1 9^n\ (mod\ 8) = 1 :

We will define the following notation, for an arbitrary n n , let { a ˉ } = { b Z + : b ( m o d x ) = a ( m o d x ) } \{\bar{a}\} = \{ b\ \in \mathbb{Z}^+ : b\ (mod\ x) = a\ (mod\ x) \} , and let a ˉ \bar{a} an arbitrary element of { a ˉ } \{\bar{a}\} . Note that any two numbers, r , s r, s in { a ˉ } \{\bar{a}\} will have the same remainder, or r ˉ ( m o d x ) = s ˉ ( m o d x ) \bar{r}\ (mod\ x) = \bar{s}\ (mod\ x) .

Thus, in mod 8, 9 ˉ \bar{9} is in the same set as 1 ˉ \bar{1} , and because 1 is the simplest value of that set, 9 ( m o d 8 ) = 1 9\ (mod\ 8) = 1 .

Lemma 1: a ˉ b ˉ \bar{a} \cdot \bar{b} is in the same set as a b \overline{ab} .

We know that a ˉ = n x + a \bar{a} = nx + a , and that b ˉ = m x + b \bar{b} = mx + b , with n , m Z + n,m\ \in \mathbb{Z}^+ .

Thus a ˉ b ˉ = ( n x + a ) ( m x + b ) = n m x 2 + n b x + m a x + a b = ( n m x + n b + m a ) x + ( a b ) . \bar{a} \cdot \bar{b} = (nx + a)(mx + b) \\ = nmx^2 + nbx + max + ab \\ = (nmx + nb + ma)x + (ab).

If we know that r ˉ = s x + r \bar{r} = sx + r , then we also know that given some s x + r sx + r , it will be in the same set as r ˉ \bar{r} . Let s = ( n m x + n b + m a ) , r = ( a b ) s = (nmx + nb + ma), r = (ab) .

a ˉ + b ˉ = s x + r = r ˉ = a b \bar{a} + \bar{b} = sx + r = \bar{r} = \overline{ab} . Lemma proved.

Thus, given a b ( m o d x ) \overline{ab}\ (mod\ x) , we may reduce it to a ˉ b ˉ ( m o d x ) \bar{a}\cdot\bar{b}\ (mod\ x) .

Extending this logic, p = 9 n ( m o d 8 ) = 9 9 . . . n t i m e s = 9 ˉ ( m o d 8 ) 9 ˉ ( m o d 8 ) . . . n t i m e s = 1 1 1 . . . n t i m e s = 1. p = \overline{9^n} (mod\ 8) = \overline{9 \cdot 9\ ... n\ times} \\ = \bar{9}\ (mod\ 8)\cdot\bar{9}\ (mod\ 8)\ ... n\ times \\ = 1 \cdot 1 \cdot 1 \ ... n\ times = 1.

p = 1 , q = 8 p + q = 9. p = 1, q = 8 \Rightarrow p + q = 9. QED.

Actually there was no need to do all this, clearly 9 n = ( 8 + 1 ) n 9^n=(8+1)^n So by binomial theorem ( 8 + 1 ) n 1 m o d 8 (8+1)^n\equiv 1\mod 8 \implies 9 n m o d 8 = 1 9^n \mod 8 =1 \square

Parth Lohomi - 6 years, 1 month ago

Log in to reply

That's a much simpler solution. Thanks.

Akash Gaonkar - 6 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...